1977
DOI: 10.1136/gut.18.3.187
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aspirin on intestinal absorption of glucose, sodium, and water in man.

Abstract: SUMMARY The effect of aspirin on small intestinal function in six healthy volunteers was examined using a segmental perfusion technique, with a test solution of 40 mM D-glucose, 140 mM NaCl, and 0*5 % polyethylene glycol. Jejunal glucose, sodium, and water absorption rates were inhibited by 50 % after oral administration of 2-6 g aspirin. Adenosine triphosphate (ATP) concentration was assayed in jejunal mucosal biopsies before and after aspirin. There was an almost 50 %g decrease in mucosal ATP levels after as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1979
1979
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 18 publications
(16 reference statements)
0
7
0
Order By: Relevance
“…On the other hand, some studies have shown the opposite effect on energy metabolism. Jorgensen et al [20] and Arvanitakis et al [21] measured falls in ATP levels in pig gastric mucosa and human jejunal biopsies respectively after ingestion of aspirin. However, the doses used in these studies were very high, 10 g in the former and 2n6 g in the latter, both administered as a single dose.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, some studies have shown the opposite effect on energy metabolism. Jorgensen et al [20] and Arvanitakis et al [21] measured falls in ATP levels in pig gastric mucosa and human jejunal biopsies respectively after ingestion of aspirin. However, the doses used in these studies were very high, 10 g in the former and 2n6 g in the latter, both administered as a single dose.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 1B indicates a slight decrease in the serum glucose level of diabetic rats after ASA treatment. The hypoglycemic effect of ASA through the decrease in the intestinal absorption of glucose (Arvanitakis et al, 1977), reduction in the hepatic gluconeogenesis (Hundal et al, 2002), and the decrease in the insulin clearance (Hundal et al, 2002) has been reported previously in human subjects, normal or insulin resistant. However, it was pointed out that nonsteroidal antiinflammatory drugs should not be considered as therapy for hyperglycemia (Mork and Robertson, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal absorption of hexoses may be depressed in humans by biguanides (Arvanitakis et al, 1973;Caspary, 1977b), prenylamine (Caspary and Creutzfeldt, 1972;Gottesburen et al, 1974), and aspirin (Arvanitakis et al, 1977). Inhibition of sodiumdependent active hexose transport by depriving mucosal cells of energy seems to be the underlying mechanism responsible for the inhibitory action of biguanides and aspirin on intestinal glucose absorption (Arvanitakis et al, 1977;Caspary, 1977b).…”
Section: Discussionmentioning
confidence: 99%